Germplasm enhancement of maize: a look into haploid induction and chromosomal doubling of haploids from temperate‐adapted tropical sources. (4th October 2016) - Smelser, Andrew; Gardner, Candice; Blanco, Michael; Lübberstedt, Thomas; Frei, Ursula
Abstract: The allelic diversity (AD) project of the Germplasm Enhancement of Maize (GEM) programme utilized the double haploid (DH) breeding method to expedite development and release of lines derived from 300 exotic maize races. Using 18 races in this study, differential effects on haploid induction rates (HIRs) and doubling rates (DRs) by the recurrent parents PHB47 and PHZ51, the elevation that the race is traditionally grown at, and by the race itself were addressed in this study. Races from the AD project were grouped by elevation of their origin, high, middle or low altitude. Six races per elevation were randomly selected and backcrossed using both recurrent parents to generate 36 populations. Ten replications were randomized in a complete randomized design for two growing seasons. The recurrent parent effect was significant, with PHB47 having a higher HIR than PHZ51. Effect of elevation was significant with higher HIR associated with low‐elevation origin, and race also proved to be significant. Effects of elevation, recurrent parent and race were not significant for DR.